2023
DOI: 10.1021/acs.est.3c04001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite-Mediated Bacterial Antibiotic Resistance Revealed by Surface-Enhanced Raman Spectroscopy

Wei Wang,
Peter J. Vikesland

Abstract: A prompt on-site, real-time method to detect bacterial antibiotic resistance is crucial for controlling the spread of resistance. Herein, we report the use of surface-enhanced Raman spectroscopy (SERS) for the monitoring of bioactive metabolites produced by ampicillin-resistant Pseudomonas aeruginosa strains and identification of mechanisms underlying antibiotic resistance. The results indicate that the blue-green pigment pyocyanin (PYO) dominates the metabolite signals and is significantly enhanced upon expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“… Wang X. et al (2023) demonstrated the detection of E. coli using an aptamer-modified Au@macroporous magnetic silica photonic microsphere (MMSPM) 3D SERS-activated substrate. Concurrent efforts focused on monitoring bioactive metabolites secreted by ampicillin-resistant P. aeruginosa strains, revealing resistance mediated by the pigment pyoverdine (PYO) ( Wang and Vikesland, 2023 ). To mitigate the impact of silver nanoparticle size and aggregation on Raman spectroscopy signals, we employ a series of strategies, including precise control over synthesis conditions for uniform particle size, utilization of stabilizing agents to prevent aggregation, ultrasonication for temporary dispersion, and centrifugation to remove aggregates.…”
Section: Discussionmentioning
confidence: 99%
“… Wang X. et al (2023) demonstrated the detection of E. coli using an aptamer-modified Au@macroporous magnetic silica photonic microsphere (MMSPM) 3D SERS-activated substrate. Concurrent efforts focused on monitoring bioactive metabolites secreted by ampicillin-resistant P. aeruginosa strains, revealing resistance mediated by the pigment pyoverdine (PYO) ( Wang and Vikesland, 2023 ). To mitigate the impact of silver nanoparticle size and aggregation on Raman spectroscopy signals, we employ a series of strategies, including precise control over synthesis conditions for uniform particle size, utilization of stabilizing agents to prevent aggregation, ultrasonication for temporary dispersion, and centrifugation to remove aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Vikesland and colleagues employed SERS for discerning bioactive metabolites in ampicillin-resistant Pseudomonas aeruginosa strains, further illuminating antibiotic resistance mechanisms. 91 Their findings underscored the dominant role of the pigment pyocyanin (PYO), especially under subminimal inhibitory concentrations of ampicillin, offering insights into antibiotic resistance not just within the parent strain but also in cocultured bacterial strains (illustrated in Fig. 10D).…”
Section: Deciphering Metabolites and Small Molecular Entities Through...mentioning
confidence: 92%
“…Transitioning to bioactive small molecular entities, which encompass hormones, 88 neurotransmitters, 89 vitamins, 56,90 and antibiotics, 91 their pivotal roles within biological systems are undeniable. They're intricately involved in myriad processes from cellular proliferation to neural transmission.…”
Section: Deciphering Metabolites and Small Molecular Entities Through...mentioning
confidence: 99%
See 2 more Smart Citations